Actio Pauliana as the Rights Protection Efforts for Creditors in the Bankruptcy Case - Pangestu, Puja Dwi (JOURNAL OF PRIVATE AND COMMERCIAL LAW, 2019)
The implementation of a debt agreement is often found in bad faith by the debtor where the debtor is unable to pay off his debts. When the debtor is deemed unable to pay off all of his debt, the debtor can voluntarily submit palitit to the Commercial Court. Submission of bankruptcy can also be applied by creditors, of course, bankruptcy permits by debtors or creditors must fulfill the conditions mandated in the bankruptcy law. When debtors are declared bankrupt, all assets owned by the debtor are collateral for their debts.However, in its implementation, it is often found that ill will is carried out by the debtor, namely when the debtor feels that he is no longer able to repay his debts, the debtor transfers his assets to the third party for his own benefit. To protect the interests of each creditor then curator can make an action with actio pauliana, , Actio Pauliana is cancellation of all of the legal action of the assets taken by debtors. The research objective of this article is to know and understand the bankruptcy determination process based on the Bankruptcy Act and how actio pauliana attempts to protect the rights of each creditor.